2000
DOI: 10.1159/000047431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Experimental Fluorosis on the Surface Topography of Developing Enamel Crystals

Abstract: Dental fluorosis is an increasing problem, yet the precise mechanism by which fluoride exerts its effects remains obscure. In the present study, we have used atomic force microscopy to image and quantitate surface features of enamel crystals isolated from specific developmental stages of fluorotic and control rat incisors. The results showed a significant decrease in crystal surface roughness with development in control tissue. Crystals from fluorotic tissue were significantly rougher than controls at all stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…That these represent crystal forerunners was supported by high resolution AFM height images of deproteinated maturation enamel crystals (Kirkham et al, 2001). AFM images revealed contiguous 30–50 nM diameter swellings along crystal surfaces presumably representing mineralized replacements of original matrix -mineral structures, Figure 1B.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…That these represent crystal forerunners was supported by high resolution AFM height images of deproteinated maturation enamel crystals (Kirkham et al, 2001). AFM images revealed contiguous 30–50 nM diameter swellings along crystal surfaces presumably representing mineralized replacements of original matrix -mineral structures, Figure 1B.…”
Section: Resultsmentioning
confidence: 95%
“…AFM was carried out as described previously (Kirkham et al, 2001; Robinson et al, 2004) using a Nanoscope III AFM (Digital Instruments) equipped with a 16E16-μm scanner and 25 μm silicon nitride cantilevers. Images were obtained in oscillating mode at 0.2 Hz below resonance with drive amplitudes in the range 300–950 mV.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in the roughness of apatite crystals surfaces in developing fluorosed enamel have been reported 6,14,19 . It was suggested that these roughened crystals could cause fluorosis because they would impair crystal growth due to changes in crystal surface chemistry and/or incomplete removal of matrix proteins.…”
Section: Introductionmentioning
confidence: 93%
“…These properties can be assessed by AFM (atomic force microscopy) imaging, which enables spatial observation of the topography of biological specimens. The correlation of topographic images with nanomechanical properties allows for the assessment of morphology and properties at the micro-and nano-meter level in three dimensions simultaneously without the need for enamel preparation [15][16][17]. Atomic force microscopy (AFM) was used to study the structural topography of enamel crystals in healthy and affected enamel [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%